2002
DOI: 10.1128/jcm.40.4.1390-1394.2002
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Human Rotavirus with G12 and P[9] Specificity in Thailand

Abstract: G12 rotavirus has not been detected anywhere in the world since the first detection of a human strain, L26 (G12, P1B[4]), in the Philippines in 1990. In this study, we isolated a human rotavirus (strain T152) with a VP7 of G12 specificity from the stool of an 11-month-old diarrheic patient in Thailand. The strain T152 exhibited a long RNA pattern and subgroup I specificity. In the comparison of the nucleotide and amino acid sequences of the VP7 gene of strain T152 with those of rotaviruses with different G typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
198
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(211 citation statements)
references
References 26 publications
9
198
2
Order By: Relevance
“…Compared to the other NSP5/6 sequences deposited in the GenBank database, the CMH079/05 showed the highest degree of sequence identity with human rotavirus strain T152, which was isolated previously in Bangkok, Thailand, in 1998 [Pongsuwanna et al, 2002]. Phylogenetic analysis of the NSP5/6 gene also revealed that the CMH079/05 strain clustered in an exclusive branch with the T152 rotavirus strain (Fig.…”
Section: Analysis Of Vp6 Nsp4 and Nsp5/6 Gene Sequencesmentioning
confidence: 86%
See 1 more Smart Citation
“…Compared to the other NSP5/6 sequences deposited in the GenBank database, the CMH079/05 showed the highest degree of sequence identity with human rotavirus strain T152, which was isolated previously in Bangkok, Thailand, in 1998 [Pongsuwanna et al, 2002]. Phylogenetic analysis of the NSP5/6 gene also revealed that the CMH079/05 strain clustered in an exclusive branch with the T152 rotavirus strain (Fig.…”
Section: Analysis Of Vp6 Nsp4 and Nsp5/6 Gene Sequencesmentioning
confidence: 86%
“…Additionally, the detections of multiple combinations of G3 with several P genotypes such as G3P[3] [Khamrin et al, 2006a], G3P[9] [Khamrin et al, 2007b], G3P[10] (in the present study), and G3P[19] [Maneekarn et al, 2006] in the same geographical area (Chiang Mai City) suggests that reassortment events among rotaviruses circulating in that area are taken place frequently. Furthermore, analysis of the NSP5/6 sequence of CMH079/05 revealed that it was most closely related with that of T152, a G12P[9] human rotavirus strain isolated in 1998 from an 11-month-old child admitted to hospital in Bangkok, Thailand [Pongsuwanna et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Serotype G12 strains were first detected in children in Philippines between December 1987 and February 1988 Urasawa et al, 1990]. Sporadic detection of G12 strains followed in 1998-1999 in Washington, USA [Griffin et al, 2002], between 1998 and 1999 in Thailand [Pongsuwanna et al, 2002] and in 1999 in Argentina [Castello et al, 2006]. In Bangladesh and India, G12 strains were first detected sporadically in 2000 and 2001, respectively [Das et al, 2003;Rahman et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…G12 strains subsequently detected revealed a multitude of genome organizations including a long electropherotype and P[9] specificity [Pongsuwanna et al, 2002], a short electropherotype and P[6] specificity [Griffin et al, 2002] and long electropherotypes and P[6] specificity [Das et al, 2003]. G12 strains have also been recently detected with P[8] specificity and appear to reassort frequently [Banerjee et al, 2007], mimicking the ''promiscuous'' nature of G9 strains during their global emergence.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000, G12 HRV strains have been reported in Japan, Thailand, USA, India, Bangladesh (accession number DQ482723), and Argentina [Griffin et al, 2002;Pongsuwanna et al, 2002;Das et al, 2003;Shinozaki et al, 2004;Castello et al, 2006;Samajdar et al, 2006]. Two of the most recent reports have come from surveillance studies conducted in Argentina and eastern India, where G12 HRV strain was found in 6.7% and 17.1% of samples, respectively, suggesting that this is an emerging rotavirus strain [Castello et al, 2006;Samajdar et al, 2006].…”
Section: Introductionmentioning
confidence: 99%